Analisis Literasi Media dan Etika dalam Produksi Konten Dakwah di Media Sosial Islam - Muhammad Raus; Achmad Pujiono; Sepnu Andriono; Naufal Budi Saputra (Khulasah : Islamic Studies Journal, 2026)
The development of social media has transformed digital spaces into important arenas for the production, distribution, and negotiation of religious messages. This development offers significant opportunities for Islamic preaching to reach broader audiences; however, it also generates risks, including the circulation of unverified religious information, oversimplification of messages, religious commodification, polarization, and unethical communication practices. This study aims to analyze the relationship between media literacy and Islamic communication ethics in the production of Islamic preaching content on social media and to formulate an ethical-literacy model as a guideline for digital da’wah content production. The study employs a qualitative library research approach through an integrative literature synthesis and thematic analysis of 40 references published between 2021 and 2026. The data were analyzed through thematic reading, open coding, axial coding, selective coding, and argumentative synthesis. The findings indicate that media literacy for da’wah content creators includes technical, critical, and ethical competencies in verifying sources, understanding platform characteristics and algorithms, mapping audiences, selecting appropriate formats, and evaluating public responses. Islamic communication ethics functions as a value orientation through the principles of honesty, trustworthiness, wisdom, politeness, moderation, and social responsibility. This study proposes an ethical-literacy model consisting of seven stages: source verification, clarity of intention, audience mapping, format selection, language moderation, source transparency, and post-publication evaluation. The model may serve as a practical guideline for da’wah content creators, Islamic institutions, students of Islamic Communication and Broadcasting, and managers of Islamic social media accounts in producing content that is accurate, communicative, inclusive, and responsible.